Improved Correlation between Instrumental and Sensory Texture of Boiled Sweetpotato - Nakitto, M.; Ayetigbo, O.; Moyo, M.; Ssali, R.T. (2025)
Sensory texture drives consumer liking among sweetpotato consumers globally prompting the need to integrate consumer preferences in sweetpotato breeding. The study aimed to (1) revisit correlation between sensory texture, particularly firmness and instrumental texture parameters and (2) compare instrumental texture parameters to consumer acceptability and establish thresholds. To compare sensory texture and instrumental texture, sweetpotato roots were harvested from Advanced Yield Trials (AYT) planted in season 2023B from Rwebitaba (n=17) and 2023B Elite clones from Namulonge (n=11). To compare between instrumental texture and consumer acceptability, seven genotypes of contrasting texture were grown and harvested on-station in Namulonge. Instrumental texture analysis was conducted following a TPA double compression procedure to compress pieces of cooked sweetpotato (steaming time = 25 minutes) with a dimension of 30 X30 X 20 mm. Descriptive sensory analysis was performed by trained panelists and 100 consumers participated in the consumer testing survey in Kawempe division (Kampala – Uganda) where they rated samples for firmness on 5-point just-about-right (JAR) scales. Pearson correlations was used to explore the relationship between averages of sensory texture attributes and those of instrumental texture parameters. Results indicated that instrumental texture hardness was correlated with hardness by hand (r = 0.809) and in mouth (r=0.758) as well as mealiness by hand (r=0.768) and in mouth (r=0.746). The intersection of the JAR curves corresponds to an instrumental hardness of 28N which is the ideal proposed threshold for firmness pending validation. Considering a consumer acceptability of 70%, the threshold for instrumental hardness is 52-120N. These results confirm the validity of the established instrumental texture method for evaluating boiled sweetpotato quality.